Congenital Club Foot Treated By Of Ponseti Method : A Short-Term Results - Al- Edanni, Mohammed Shihab Ahmed (AL-Kindy College Medical Journal, 2019)
Background: Congenital club foot is a complex deformity of foot .It is a collection of different abnormalities, with different etiologies. Consequently, Severity varies with   difficulties in evaluating treatment strategies with outcome results. The treatment of congenital club foot remains controversial. Usually, the orthopedist's goal is to obtain anatomically and functionally normal feet in all patients.                                Objective: To asses short term follow up result of conservatively treated club feet in relation to the age of initial casting by Ponseti technique.          Methods :A cross sectional observational study with some comparative content done in Al-kindy teaching hospital .A total of 36 patients (44 clubfeet) were treated by Ponseti method during the period of October 2014 to April 2017and were studied prospectively (mean follow up period 6 months, minimum follow-up period of 3 months) . Twenty six patients were male, thus male to female ratio is 2.6 : 1. It involved only patients less than two months. The patients were divided in to two groups: Group (A) included patients less than 4 weeks, while Group (B) between 4-8 weeks of age at the initiation of the treatment. gender, bilateralism, severity of the initial clubfoot deformity measured by Pirani Severity Score System, total numbers of Ponseti casts before the tenotomy, details of tenotomy, compliance with brace were examined. Passive range of movements and look of club foot are evaluated with mean six months follow-up.                                            Results: We followed the functional Pirani Severity Scoring System and got good to excellent results in 32 patients  88.9 % (37 clubfeet – 84.1%) at mean 6 months of follow up. Ten patients  27.8 % (12 clubfeet – 27.3%) had relapse at varying age; out of which 6 patients  60% (8clubfeet  66.7%) were corrected by Ponseti casting method, while 4 patients 40% (4 clubfeet 33.3%) were resistant to Ponseti method. Poor compliance with the Denis Browne splint and poor cast technique was thought to be the main cause of failure in these patients.                                                                                 Conclusion: Good understanding the main pathology of club foot, and the ideal method of conservative treatment for correction of the deformities systematically before starting the treatment.   In all types of club foot, we start conservative treatment, either as a definite treatment or to make surgical treatment easier for the surgeon and the patient. So Starting the treatment from the first day of life give excellent results and it will be decreased with delay.